SATIRE POLITIK DAN AGAMA DALAM NOVEL GULLIVER'S TRAVELS OLEH JONATHAN SWIFT - Maya Kurnia Dewi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
The Age of Enlightenment spread in Western Europe, Britain and American colonies in the eighteenth century. This period put emphasis in scientific ideas, skepticism, and critics about the abuse of power done by government and church. Literary works in this period contain classical critics, such as the using of satire, good diction and couplet. Gulliver’s travels was written by Jonathan Swift in this period. He used the character named Gulliver who sailed to some imaginative islands, Swift criticized political and religious conditions in Britain through satires. This research discussed the correlation between Jonathan Swift as a satire writer with political and religious satires in Gulliver’s Travels. The purpose of this research was to know the political and religious problems in the age of enlightenment in Britain, to know the efforts of Jonathan Swift to criticize the conditions thorugh his satires. The method of this research used literary sociology to discuss the problems. It can be concluded that Swift criticized used Gulliver and his voyages to Liliput as a representation of political and religious problems in Britain in 18th century. The king’s minister, Walpole dominated the power to rule the government over King George II. While for the religious matters, the dispute caused by religious matters often asked many people’s lives. Through his satires and humours, Swift expected that the King and government could do some actions to solve the problems in the country.  Keywords: Jonathan Swift, the age of enlightenment, political and religious satires.